Pictorial guide to resistance training exercises
UPPER BODY EXERCISES (Pectoralis, Lattisimus Dorsi, Trapezius, Neck Musculature, Rhomboids, Deltoids, Rotator Cuff, Biceps, Triceps, Forearms, Grip Training) CORE BODY EXERCISES (Rectus Abdominus, Transverse Abdominus, Internal Obliques, External Obliques, Psoas Major & Minor, Illiacus, Lumbar Musculature, Rectus Femoris) LOWER BODY EXERCISES (Quadriceps, Hamstrings, Adductors, Abductors, Glutes, Gastrocnemius, Soleus, Tibealis Anterior, Foot, Ankle & Toe Musculature)